De Novo Assembly and Transcriptome Analysis of Contrasting Sugarcane Varieties - Cardoso-Silva, Claudio Benicio (Public Library of Science, 2014)
Sugarcane is an important crop and a major source of sugar and alcohol. In this study, we performed de novo assembly and transcriptome annotation for six sugarcane genotypes involved in bi-parental crosses. The de novo assembly of the sugarcane transcriptome was performed using short reads generated using the Illumina RNA-Seq platform. We produced more than 400 million reads, which were assembled into 72,269 unigenes. Based on a similarity search, the unigenes showed significant similarity to more than 28,788 sorghum proteins, including a set of 5,272 unigenes that are not present in the public sugarcane EST databases; many of these unigenes are likely putative undescribed sugarcane genes. From this collection of unigenes, a large number of molecular markers were identified, including 5,106 simple sequence repeats (SSRs) and 708,125 single-nucleotide polymorphisms (SNPs). This new dataset will be a useful resource for future genetic and genomic studies in this species.